العلوم المعرفية أو أركيولوجيا البحث في أنظمة التمثيل - زاوية نظر فرانسيسكو فاريلا- Cognitive scienceAn archeological research in the systems of representationFrancisco Varela’s approach (مجلة إحالات, 2025)
تقوم وجهة النظر المعرفية عبر التخصصية للفيلسوف وعالم الأحياء الشيلي فرانسيسكو فاريلا غارسيا المتعلقة بنشأة وتطور العلوم المعرفية على التشريح المقطعي لسيرورة البحث العلمي في حقل علوم العقل في علاقته بالتجارب الانسانية ، وهو تشريح يميز بين أربع مراحل أو مجالات عمل تعاقبت الواحدة تلو الأخرى خلال القرن العشرين هي : مرحلة البدايات: ميلاد العلوم وتكنولوجيا المعرفة ،المرحلة الثانية : الرموز : الفرضية المعرفية ،المرحلة الثالثة : مرحلة الانبثاق : ظهور البدائل في معالجة الرموز، المرحلة الرابعة : الانتظام الذهني/الخارجي أو مرحلة البدائل في سيرورة التمثيل. يفصل هذا البحث في هذه المراحل مثلما يعرضها فرانسيسكو فاريلا في واحد من أهم كتبه "مقدمة إلى العلوم المعرفية" الذي يقول عنه أنه "جولة إرشادية منظمة لحقل متعدد التخصصات" نخلص منها إلى استكشاف التكامل في العلاقات المتبادلة بين الظواهر البيولوجية والفيزيائية والاجتماعية والثقافية .The interdisciplinary cognitive point of view of the Chilean philosopher and biologist Francisco Varela García related to the origins and development of cognitive sciences is based on cross-sectional anatomy of the process of scientific research in the field of mind sciences in relation to human experiences, which is a sort of anatomy that distinguishes between four different stages or areas of work that have alternated one after the other during the twentieth century. First stage: the beginnings ; which is the stage of the the birth of STC ( science and technology of cognition), the second stage: the symbols: the cognitive hypothesis, the third stage the emergence stage: the emergence of alternatives in symbol processing, and finally, the fourth stage: the enaction or the alternatives stage in the representation process This research details these stages, as presented in Francisco Varela’s famous book " Cognitive Sciences ; a cartography of current ideas", which is prsented by his author as "an organized guided tour of an interdisciplinary field" from which we get the rich experiment about the complementarity in the interrelationships between biological, physical, social and cultural phenomena in human life